Introduction - Caliman Campos, Ludimila (Romanitas - Revista de Estudos Grecolatinos, 2021)
Introduction of the dossier: "Images of power and power of images in the Roman World".
Keywords: Introduction; Dossier; Images of power and power of images in the Roman World